THE EFFECTS OF CABLE CHARACTERISTICS ON MAXIMUM OVERVOLTAGE IN COMBINED OVERHEAD/CABLE LINES PROTECTED BY SURGE ARRESTERS - Alizadeh, Reza; Mirzaie, Mohammad (IIUM Engineering Journal, 2018)
Â This paper presents the calculation of maximum lightning overvoltage for a transmission system consisting of overhead lines in combination with an underground power cable. For this purpose, a 132 kV overhead transmission line combined with an underground cable is considered. This combined line has been protected by surge arresters. EMTP-RV and MATLAB software are used to conduct the modeling, simulation and calculation works. Lightning strikes on the tower top and results in large over-voltages appearing along overhead lines and cable. Underground cable characteristics have significant effects on maximum lightning over-voltages. Therefore, the three characteristics considered for these effects are: (i) cable length; (ii) cable core resistivity, (iii) cable sheath resistivity. Tower footing resistance effect is also included in the computer simulation. ABSTRAK: Kajian ini berkenaan tentang pengiraan takat maksimum voltan kilat berlebihan bagi sistem transmisi melibatkan kabel atas kepala termasuk kabel tenaga bawah tanah. Bagi tujuan ini, talian kabel penghantaran atas kepala 132 kV termasuk kabel bawah tanah telah diambil kira. Kombinasi kabel ini dilindungi dengan penahan lonjakan voltan tenaga. Perisian EMTP-RV dan MATLAB telah digunakan untuk membuat model, simulasi dan kerja-kerja pengiraan. Panahan petir di atas puncak bangunan merupakan penyebab utama voltan berlebihan muncul bersama talian atas kepala dan kabel. Ciri-ciri kabel bawah tanah merupakan faktor penyumbang utama ke atas voltan berlebihan daripada kilat. Oleh itu, tiga kes telah diambil kira sebagai penyumbang voltan berlebihan: (i) panjang kabel; (ii) rintangan teras kabel, (iii) rintangan sarung kabel. Kesan rintangan tapak bangunan turut diambil kira dalam simulasi komputer.